Paróquia Verbo Encarnado: jovens cantores em muda vocal - Barbosa, Luciana Andrade Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This paper discusses about the characteristics of teenagers in changing voice. My goal is to explore some of the studies of the characteristics about the changing voice and see which one are present or absent in a group of singers adolescents. Therefore, a literature review on this subject was held, pointing out the characteristics that each author presents in his work. Then I conducted a case study with ten teenage singers in changing voice at the Incarnate Word church in Santo Amaro, applying vocalizes and listening to songs, in order to observe which features their voices had and what their extensions and tessitura. Finally, there was the comparison of information from the literature review with case study information, pointing out the similar and different characteristics, discussing each result. I conclude with this study that the general characteristics of vocal changes are presented in most cases, but it is necessary to analyze eac h case to determine the best way to deal with the voice of adolescents, so that they have a healthy vocal change and painlessly

O presente trabalho trata das características da voz de adolescentes em muda vocal. Tenho como objetivo explorar parte dos estudos sobre as características acerca da muda vocal e verificar quais estão presentes ou ausentes em um grupo de adolescentes cantores. Para isso, realizei uma revisão bibliográfica acerca do assunto, apontando as características que cada autor apresenta em sua obra. Em seguida realizei um estudo de caso com dez adolescentes cantores em muda vocal da paróquia Verbo Encarnado, em Santo Amaro, aplicando vocalizes e ouvindo canções, com a finalidade de observar quais características suas vozes apresentavam e quais eram suas extensões e tessituras. Por fim, realizei a comparação dos dados da revisão bibliográfica com os dados do estudo de caso, apontando as características semelhantes e diferentes, discutindo sobre cada resultado. Concluo com esse estudo que as características gerais da muda vocal estão presentes em sua maioria, porém é preciso analisar cada caso para determinar qual a melhor forma de lidar com a voz dos adolescentes, de forma que tenham uma muda vocal saudável e sem traumas
Keywords: Musica vocal; Música e adolescentes; Música sacra vocal; Adolescentes; Music and teenagers